Behaviours associated with weight loss maintenance and regaining in a Mediterranean population sample. A qualitative study. Issue 5 (23rd August 2013) - Karfopoulou, E.; Mouliou, K.; Koutras, Y.; Yannakoulia, M.
Summary: What is already known about this subject: In the US, the National Weight Control Registry revealed lifestyle behaviours shared by weight loss maintainers. In the US and the UK, qualitative studies compared the experiences of weight loss maintainers and regainers. High rates of physical activity, a low‐energy/low‐fat diet, weight self‐monitoring, breakfast consumption and flexible control of eating are well‐established maintenance behaviours. What this study adds: The Mediterranean lifestyle has not been studied relative to weight loss maintenance. This study focused on a sample of Greek maintainers and regainers. Maintainers emphasized home‐cooked meals; their diet does not appear to be low‐fat, as home‐cooked Greek meals are rich in olive oil. Having a small dinner is a common strategy among maintainers. Health motives were not mentioned by maintainers. Maintainers, but not regainers, appeared to compensate for emotional eating. Weight loss maintenance is imperative to successful obesity treatment. We qualitatively explored lifestyle behaviours associated with weight regulation, in a sample of Greek volunteers who had lost weight and either maintained or regained it. A 10% intentional loss maintained for at least one year was considered successful maintenance. Volunteers ( n = 44, 41% men) formed eight focus groups, four of maintainers and four of regainers. Questions regarded weight loss, weight maintenance or regaining, and beliefs on weight maintenance and regaining. All discussions were tape recorded. Maintainers lost weight on their own, whereas regainers sought professional help. Maintainers exercised during both the loss and maintenance phases, whereas regainers showed inconsistent physical activity levels. Health motives for weight loss were mentioned only by regainers. Emotional eating was a common barrier, but only maintainers compensated for it. Maintainers continuously applied specific strategies to maintain their weight: emphasizing home‐cooked meals, high eating frequency, a small dinner, portion size regulation, and sweets' intake regulation. Regainers considered the behaviours leading to weight loss different from their normal lifestyle, and resumed their old habits when the diet was over. However, both groups believed that for long‐term success, lifestyle changes need to be permanent.